From “Outsider” to Insider: The Case of Reliance - Surajit Mazumdar (South Asia Multidisciplinary Academic Journal)
At the time of India’s liberalization, the Reliance group was already one of India’s leading business groups and in subsequent years it has only solidified its place at the top of India’s corporate hierarchy. Reliance was not, however, among the “traditional” large groups that emerged during the colonial era and remained dominant in the mid-1960s. This paper traces the story of the Reliance phenomenon and briefly discusses the process (method) by which that story was constructed. In addition to demystifying the phenomenon, the paper seeks to demonstrate there is sufficient evidence available to assert that the basis for the success of Reliance was fundamentally no different from that which other groups used to perpetuate their dominant position, and that the roots of this success lay in the nature of Indian capitalism.